In Silico Exploration of Orthosiphon stamineus Compounds as Potential Angiotensin Receptor Blockers for Hypertension Therapy - Prasetiyo, Andri; Indriani, Aqilah Idelia; Ramadhani, Karina Natasya; Natthawani, Amitta; Ramadhan, Islami Al-Kaffah; Yogaswara, Amira Thufailla; Audrey, Cresentia; Mulatsari, Esti; Mumpuni, Esti; Zahra, Nurulita Az (Jurnal Jamu Indonesia, 2025)
Orthosiphon stamineus has demonstrated antihypertensive potential, but the specific bioactive compounds involved remain unclear. This study aimed to evaluate selected phytochemicals from O. stamineus as angiotensin receptor blockers (ARBs) targeting protein 4ZUD using in-silico methods. Molecular docking was conducted to assess binding affinity, while ADMET analysis evaluated pharmacokinetics and toxicity. Salvianolic acid E showed the strongest binding affinity with a rerank score of −134.02 kcal/mol, surpassing olmesartan (−124.52 kcal/mol). Key interactions were observed with amino acid residues Arg167, Tyr92, and Asp281. ADMET predictions revealed that Salvianolic acid E has good aqueous solubility, moderate intestinal absorption (HIA 45.99%), and low membrane permeability (Caco-2 < 0.4). It does not inhibit major cytochrome P450 isoenzymes and is predicted to be non-hepatotoxic, suggesting favorable safety and metabolic profiles. These findings highlight Salvianolic acid E as a promising phytochemical candidate for antihypertensive drug development.